Association of semaglutide use with depressive symptoms and suicidal behavior in a patient with type 2 diabetes: A case report - Anisija Stojkovska; Polona Rus Prelog; Anja Kokalj Palandacic (Journal of International Medical Research)
Semaglutide is a glucagon-like peptide-1 receptor agonist used in the treatment of type 2 diabetes mellitus and management of obesity. Associations of glucagon-like peptide-1 receptor agonist use with psychiatric adverse events and suicidal behavior have been reported. A man in his late 70s with type 2 diabetes and no history of psychiatric illness or cognitive deficits was admitted to our clinic after his first suicide attempt involving the impulsive ingestion of brush cleaner liquid. A month before his presentation, he reported restlessness and depressive mood without any apparent trigger. This period was consistent with the time of semaglutide introduction. His psychiatric symptoms improved after semaglutide discontinuation. This case report highlights the importance of regular monitoring of depression and anxiety symptoms and the possibility of suicidal ideation in individuals with type 2 diabetes treated with semaglutide. This may enable early detection and prevention of serious psychiatric adverse events.